2011
DOI: 10.1177/0003319711400183
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Increased Carotid Intima-Media Thickness and Being Nondipper in Nonobese and Normotensive Young Patients Affected by PCOS

Abstract: Polycystic ovary syndrome (PCOS) is characterized by chronic unovulation, hyperandrogenism, and insulin resistance. We evaluated factors that affect "nondipper" status during 24-hour ambulatory blood pressure monitoring (ABPM) and carotid intima-media thickness (cIMT) in PCOS. Forty-two nonobese women newly diagnosed as PCOS and 32 healthy women were included. After biochemical and hormonal measurements, the ovaries were imaged by pelvic ultrasonography and cIMT was measured by B-mode ultrasonography. A 24-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…Our observations are in agreement with previous findings in adolescents with PCOS [53][54][55][56]. High IMT values in PCOS were reported in women in early adulthood (associated with decreased sex hormone-binding globulin) [57] and adulthood [58][59][60][61][62][63][64][65] in obese women [50,66,67] and patients with juvenile rheumatoid arthritis [68]. Our study participants were adolescent and young adult women with PCOS and proper controls matched for BMI, so as to overcome the strong confounding associations of age and BMI with arterial thickness in PCOS [68].…”
Section: Commentsupporting
confidence: 93%
“…Our observations are in agreement with previous findings in adolescents with PCOS [53][54][55][56]. High IMT values in PCOS were reported in women in early adulthood (associated with decreased sex hormone-binding globulin) [57] and adulthood [58][59][60][61][62][63][64][65] in obese women [50,66,67] and patients with juvenile rheumatoid arthritis [68]. Our study participants were adolescent and young adult women with PCOS and proper controls matched for BMI, so as to overcome the strong confounding associations of age and BMI with arterial thickness in PCOS [68].…”
Section: Commentsupporting
confidence: 93%
“…Insulin resistance and hyperinsulinism have been known as pathogenetic mechanisms for the last 15 years, present in 50-70% of these women, whereas MetS prevalence is higher than in age and weight-matched controls [85]. Even in the absence of obesity or MetS, these patients may have insulin resistance and increased cardiovascular risk [86]. High insulin levels affect the hypothalamus-pituitary-ovarian function, as well as glucose utilization in peripheral tissues [87].…”
Section: Metformin In Polycystic Ovary Syndromementioning
confidence: 99%
“…33 35 Third, a recent study reported that arterial stiffness, a novel risk factor for future CVD, 36 was more common in PCOS participants in their 20s. 37 Fourth, carotid intima–media thickness was higher in women with PCOS 38 and in women over 45 years with a history of PCOS. 39 In the same study, no clue for clinical atherosclerosis could be detected in women with PCOS aged between 30 and 44 years.…”
Section: Discussionmentioning
confidence: 94%